2024
DOI: 10.1186/s12889-024-17791-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding factors influencing people with disabilities’ participation in sports and cultural activities

Ming Chen,
Qianxue Li,
Luqi Wang

Abstract: Background Improving people with disabilities’ participation in sports and cultural activities benefits their physical and mental health. However, only a few studies have examined the factors that influence participation systematically. Methods Using the survey data gathered from 4,319 disabled people living in a district in Wuhan, China, this study explored the impacts of sports and cultural activity participation in terms of individual physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Differentiating between being introduced to sports and learning values through sports provides a deeper understanding of why people engage in sports. This socialisation process is influenced by a combination of external factors such as location, culture, and available sporting opportunities, as well as internal factors including self-perception, life stage, learning processes, perception, motivation, attitude, and physical traits ( Mullin et al, 2000 ; Ruddell and Shinew, 2006 ; Seal, 2012 ; Sales and Misener, 2021 ; Alhumaid et al, 2022 ; Chen et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differentiating between being introduced to sports and learning values through sports provides a deeper understanding of why people engage in sports. This socialisation process is influenced by a combination of external factors such as location, culture, and available sporting opportunities, as well as internal factors including self-perception, life stage, learning processes, perception, motivation, attitude, and physical traits ( Mullin et al, 2000 ; Ruddell and Shinew, 2006 ; Seal, 2012 ; Sales and Misener, 2021 ; Alhumaid et al, 2022 ; Chen et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…This includes not only physical accessibility but also the provision of adaptive equipment and knowledgeable coaches who understand the nuances of training women athletes with physical impairment. Empowering women with physical impairments in Para sports goes beyond merely providing opportunities; it involves creating an inclusive ecosystem that celebrates diversity, recognizes individual capabilities, and promotes a culture of equality ( Nagata, 2008 ; Chen et al, 2024 ). This study supports the study by Olenik et al (1995) that identified the underrepresentation of women in Para sports, both as athletes and in administrative roles, remains a significant barrier to raising awareness about the unique challenges faced by women athletes with physcal impairments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation